Specificity of peptidases secreted by filamentous fungi. Issue 1 (1st January 2018) - Hamin Neto, Youssef Ali Abou; da Rosa Garzon, Nathália Gonsales; Pedezzi, Rafael; Cabral, Hamilton
ABSTRACT: Peptidases are enzymes that cleave peptide bonds, yielding proteins and peptides. Enzymes in this class also perform several other functions, regulating the activation or inactivation of target substrates via proteolysis. Owing to these functions, peptidases have been extensively used in industrial and biotechnological applications. Given their potential functions, it is important to optimize the use of these enzymes, which requires determination of the specificity of each peptidase. The peptidase specificity must be taken into account in choosing a peptidase to catalyze the available protein source within the desired application. The specificity of a peptidase defines the profile of enzyme–substrate interactions, and for this the catalytic site and the arrangement of the amino acid residues involved in peptide bond cleavage need to be known. The catalytic sites of peptidases may be composed of several subsites that interact with amino acid residues for proteolysis. Filamentous fungi produce peptidases with varying specificity, and here we provide a review of those reported to date and their potential applications.